Periaeschna yazhenae sp. nov. from Fujian, China (Odonata: Anisoptera: Aeshnidae) - Xu, Qi-Han (Zootaxa, 2012)
A new species of the genus Periaeschna Martin, P. yazhenae sp. nov. from Fujian, China is described, illustrated and diagnosed from its congeners. Description of the final stadium larva of the new species is also provided. The new species is closely similar to P. zhangzhouensis Xu 2007 due to the high similarity of anal appendages, but is easy to separate from that species by the following characters: distal 1/4 of cercus narrowest and with truncated apex; abdominal segments 1–9 with simpler and less developed dorsal markings and with more complicated and more developed ventrolateral and ventral markings; and wings tinted with brownish-black at extreme base.